Asistensi Pembuatan Website “Mall Pelayanan Publik” Dinas Penanaman Modal Dan Pelayanan Terpadu Satu Pintu Kota Samarinda - Bambang Irawan; Muhammad Nizar Hidayat (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2021)
The existence of a government website is an initial milestone in the implementation of e-government as an official channel for the dissemination of information related to public services. However, there are still some OPDs that do not have an official website, such as the Samarinda City DPMPTSP which does not yet have a special website related to “Public Service Malls”. This is suspected to be due to the lack of competent human resources in managing the government's official website. Based on this, community service this time is intended to provide assistance to the Samarinda City DPMPTSP in terms of making the official website "Public Service Mall" as a form of efforts to strengthen e-government within the Samarinda City Government. This PkM activity is carried out using thematic assistance and training methods